2013
DOI: 10.4103/2141-9248.122119
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal effect of misgav ladach cesarean section in Nigerian Women: A randomized control study

Abstract: Background:The poor utilisation of the Misgav-Ladach (ML) caesarean section method in our environment despite its proven advantage has been attributed to several factors including its non-evaluation. A well designed and conducted trial is needed to provide evidence to convince clinician of its advantage over Pfannenstiel based methods.Aim:To evaluate the outcome of ML based caesarean section among Nigerian women.Subjects and Methods:Randomised controlled open label study of 323 women undergoing primary caesare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Eight studies reported on analgesia use 21–23,26,31,33,41,44 . No difference was seen between MMLM and PKM (MD: −0.99 doses, 95% CI: −2.53, 0.54, Tau 2 = 2.44, I 2 = 100%) (Figure 2G1).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Eight studies reported on analgesia use 21–23,26,31,33,41,44 . No difference was seen between MMLM and PKM (MD: −0.99 doses, 95% CI: −2.53, 0.54, Tau 2 = 2.44, I 2 = 100%) (Figure 2G1).…”
Section: Resultsmentioning
confidence: 97%
“…The total number of patients that underwent CS were 15 251. Of these, 5809 (38.1%) underwent PKM, 10,19–44 3790 (24.9%) MLM, 21,23,25,27,30–32,34–36,38–41,43 and 5597 (36.7%) MMLM 10,19,20,22,24,26,28,29,33,36,42,44 . The range of means for ages of the entire maternal cohort was 23.16–32.33 years and the gestational cohort was 36.50–39.24 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is similar to the study of Lyell et al Lyell and other studies in which the rate of adhesion was more in the previous caesarian section. 15,[24][25][26] In the study of Bhowmk et al difficulty in opening the abdomen was countered in 74 patients (41.11%) because of adhesive between the uterus and undersurface of the rectus sheath. 27 Difficulty in the separation of the bladder was seen in 24% (13.33%) patients.…”
Section: Discussionmentioning
confidence: 99%